2021
DOI: 10.3389/fmicb.2020.579593
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Nucleolar Localization of Bovine Adenovirus-3 Protein V

Abstract: The L2 region of bovine adenovirus-3 (BAdV-3) encodes a Mastadenovirus genus-specific protein, designated as pV, which is important for the production of progeny viruses. Here, we demonstrate that BAdV-3 pV, expressed as 55 kDa protein, localizes to the nucleus and specifically targets nucleolus of the infected cells. Analysis of deletion mutants of pV suggested that amino acids 81–120, 190–210, and 380–389 act as multiple nuclear localization signals (NLS), which also appear to serve as the binding sites for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…However, a recent report suggests that although pV is bound to the incoming viral genome, it dissociates from the virus partly at the entry of the AdV core in the cytoplasm and at the nuclear pore complex [59] without entering the nucleus. In contrast, newly synthesized pV actively transports to the nucleus with the help of its own nuclear localization signals (NLSs) by utilizing α/β nuclear import receptor-mediated nuclear transport machinery [76,77]. While a number of studies have reported the presence of both monopartite [76,77] and/or bipartite [76] NLSs, the location of NLSs and use of nuclear receptor for nuclear transport of pV may differ among pV encoded by different members of mAdV [38,76,77].…”
Section: Protein V (Pv) 221 General Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a recent report suggests that although pV is bound to the incoming viral genome, it dissociates from the virus partly at the entry of the AdV core in the cytoplasm and at the nuclear pore complex [59] without entering the nucleus. In contrast, newly synthesized pV actively transports to the nucleus with the help of its own nuclear localization signals (NLSs) by utilizing α/β nuclear import receptor-mediated nuclear transport machinery [76,77]. While a number of studies have reported the presence of both monopartite [76,77] and/or bipartite [76] NLSs, the location of NLSs and use of nuclear receptor for nuclear transport of pV may differ among pV encoded by different members of mAdV [38,76,77].…”
Section: Protein V (Pv) 221 General Characteristicsmentioning
confidence: 99%
“…In contrast, newly synthesized pV actively transports to the nucleus with the help of its own nuclear localization signals (NLSs) by utilizing α/β nuclear import receptor-mediated nuclear transport machinery [76,77]. While a number of studies have reported the presence of both monopartite [76,77] and/or bipartite [76] NLSs, the location of NLSs and use of nuclear receptor for nuclear transport of pV may differ among pV encoded by different members of mAdV [38,76,77].…”
Section: Protein V (Pv) 221 General Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations